An unusual case of acquired reactive perforating collagenosis. - Geitoeira, S.; Soares Cardoso, S.; Rato, M.; Pimenta, J.; Antunes, J.; Couto, M.; Cabral, R. (European Journal of Pediatric Dermatology, 2023)
Reactive perforating collagenosis (RPC) is a rare condition characterized by transepidermal shedding of impaired collagen. Hereditary RPC is very rare and begins in childhood, while acquired RPC occurs in adulthood and is usually associated with systemic conditions, such as diabetes mellitus or chronic renal failure. Here was reported an unusual case of RPC in a healthy 16-year-old girl. A transient increase in creatine kinase, a temporary alteration of electromyography, and a weakly positive anti-MDA5 autoantibody was detected in the patient. Despite the specificity of the antibody for dermatomyositis, no characteristic skin lesions or muscle weakness appeared in the patient within two years of diagnosis. The importance of careful monitoring in such cases is underlined, because RPC could be the first manifestation of another not yet fully expressed condition.